Analysis Of The Effect Of The Soybean Crude Urease Calcite Precipitation (SCU-CP) Method On The Permeability Of Sandy Clay Soil - Raudah Ahmad; IGN Aditya Dhiva; Insan Kamil; Dhinar Yoga Hanggung Legowo; Jalung Alvin Leo (Journal of Civil Engineering and Planning (JCEP), 2026)
Soil with high permeability has the potential to cause seepage, which can lead to piping, ground subsidence, and structural failure. This study aims to evaluate the effectiveness of the Soybean Crude Urease Calcite Precipitation (SCU-CP) method in reducing soil permeability coefficients through a falling-head test. Soil sample A-6 was classified with a liquid limit (LL) of 39.97% and a plastic limit (PL) of 24.38%. The SCU-CP method used urea and CaCl₂ solutions at concentrations of 1 mol/L and 1.5 mol/L, with the addition of 10–30 g/L of soybean powder. The results showed that soil permeability decreased from 4.01 × 10⁻⁴ cm/s to 1.07 × 10⁻⁴ cm/s (73.32%) with the 1 mol/L reagent and to 4.77 × 10⁻⁵ cm/s (88.10%) with the 1.5 mol/L reagent, both using 30 g/L of soybean powder. These results indicate that the SCU-CP method is effective in reducing soil permeability and has the potential to serve as an environmentally friendly alternative for soil stabilization.